Integrating Tahfidz into the Islamic Religious Education Curriculum to Strengthen Qur’anic Competence - Khoir, Ummul; Munjiat, Siti Maryam (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to examine the strengthening of Qur’anic competence through its integration into the tahfidz-based Islamic Religious Education (PAI) curriculum in Indonesia. Using a literature review approach and descriptive-analytical content analysis, the study examines various scholarly sources, including books, national and international journal articles, and relevant educational policy documents. The findings indicate that Qur’anic competence is multidimensional, encompassing four interrelated domains: tilawah (the ability to recite the Qur’an accurately with proper tartil and tajwid), tahfidz (progressive memorization), contextual understanding and tadabbur (reflective contemplation), and the application of Qur’anic values in everyday life. The integration of these competencies into the PAI curriculum can be implemented through four models: the thematic-integrative model, the vertically sequenced model, the project-based model, and a school culture model that positions the Qur’an as the central foundation of the educational ecosystem. The success of integrating Qur’anic competence is influenced by four key factors: the competence and professionalism of PAI teachers, the quality of instructional materials, the leadership of school principals, and the synergy among schools, families, and communities. To ensure the sustainable strengthening of Qur’anic competence, several strategies are recommended, including the standardization of measurable competencies, technology-based pedagogical innovation, the professional development of teachers, the transformation of assessment systems into authentic and holistic forms, and the development of a comprehensive Qur’anic ecosystem within the school environment. Based on these findings, the study emphasizes that the Qur’an should not merely be treated as a formal subject but should serve as the spiritual foundation and value compass guiding the entire process of Islamic education in Indonesia.